Effect of Aromatherapy Inhalation on Therapeutic Relationship and Job Stress Levels of Psychiatric Nurses: A Randomized Controlled Study. - Türkyılmaz, Serdar; Altundal Duru, Hilal (Journal of Education & Research in Nursing / Hemşirelikte Eğitim ve Araştırma Dergisi, 2026)
Background: Psychiatric nurses experience high levels of job stress, which negatively affect therapeutic relationships. Aromatherapy has shown promise in reducing stress; however, its impact on therapeutic engagement remains underexplored. Aim: This experimental study aimed to examine the effects of aromatherapy inhalation on the therapeutic relationship and job stress levels of psychiatric nurses. Methods: This study was designed as a randomized controlled trial with a control group. Participants were randomly assigned to either the experimental group (n=33) or the control group (n=33) from among psychiatric nurses working in a psychiatric clinic in Ankara between January 1 and March 31, 2025. The experimental group received lavender essential oil inhalation three times per week on alternate days. Data were collected using the Introductory Information Form, General Job Stress Scale, and the Therapeutic Relationship Evaluation Scale–Nursing Form. Statistical analyses included the chi-square test, Independent Samples t-test, Paired Samples t-test, and Wilcoxon Signed-Rank test. Results: The groups were homogeneous; however, a statistically significant difference was found in gender distribution (p=0.027). Following lavender essential oil inhalation, the experimental group demonstrated a statistically significant increase in post-intervention therapeutic relationship scores compared to the control group (p=0.042), particularly in the "participation in care" subdimension (p=0.001). No significant difference was observed between groups in terms of job stress levels after the lavender essential oil inhalation (p>0.05). Conclusion: Aromatherapy inhalation was found to enhance the therapeutic relationship. It may support psychiatric nurses in strengthening therapeutic relationships by promoting empathy and engagement.